Diagnosis of coronary artery disease using artificial intelligence based decision support system - Noor Akhmad, Setiawan; Venkatachalam, P.A.; Ahmad Fadzil, M. Hani (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.